ROLE OF ORGANIC FERTILIZER AND BORON FOLIAR APPLICATION ON GROWTH AND PRODUCTIVITY OF POTATO FOR PROCESSING - U. B. SHAKER; I. J. ABDUL RASOOL (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This research was carried out at University of Baghdad - College of Agricultural Engineering Sciences during the fall season of 2020 and spring season of 2021 in order to evaluate the effect of organic fertilizer and the foliar application of boron on the growth and yield of industrial potatoes (Solanum tuberosum L.). Using factorial experiment (5*4) within Randomized Complete Block Design with three replicates, the organic fertilizer (palm fronds peat) was applied at four levels (0, 12, 24, and 36 ton ha-1) in addition to the treatment of the recommended of chemical fertilizer. The foliar application of Boron was applied at four concentrations which were 0, 100, 150 and 200 mg (H3Bo3). L-1. The results Revealed a significant increase under the application of organic fertilizer at the level of 24 ton.ha-1 and the foliar application of boron at a concentration of 100 mg. L-1 (O24B100) on plant height, main branches number, and leaves number, which was reflected on the increase of vegetative dry weight and then the yield of potato (63.67 cm and 57.00 cm plant-1), (4.89 and 5.22 stem. plant-1), (66.50, and 55.67 leaf. plant-1), (113.38 and 108.49 g. plant-1), (44.17 and 59.48 ton.ha-1) for both seasons, respectively. It also recorded a Significant differences in the chemical parameters in the leaves, as Chlorophyll reached (265.51 and 203.12 mg.100 g-1 wet weight), N (4.883 and 2.293%), P (0.577 and 0.413%), K (2.467 and 2.660%) and B (65.60 and 63.56 mg. kg-1) for both seasons, respectively.